Anesthetic considerations in supravalvular aortic stenosis: A case series - Virendra Kumar; Mona Swain; Ira Balakrishnan M; Vineesha G (Asian Journal of Medical Sciences, 2023)
Supravalvular aortic stenosis (SVAS), characterized by elastin arteriopathy, presents either as a localized narrowing at the sinotubular junction or as a diffuse form with additional involvement of the ascending aorta, aortic arch, and its branches. Associated lesions of the aortic valve, coronary artery narrowing, and pulmonary artery stenosis can further complicate the disease process. These patients are inherently at risk for developing myocardial ischemia, particularly in the setting of anesthesia or sedation. The left ventricular hypertrophy, secondary to the obstruction, results in increased left ventricular wall tension and myocardial oxygen consumption. Associated anatomic factors in the coronary arteries can further impair coronary blood flow. Any anesthetic drug that further increases oxygen consumption or decreases the coronary blood flow will result in an imbalance and increase the risk of cardiac arrest. We present a series of three patients with SVAS who were operated at our institute and subsequently discharged with good outcomes. The hemodynamic goal during the perioperative should aim to balance the myocardial oxygen supply-demand ratio. Extreme vigilance and aggressive resuscitative measures are needed to prevent any adverse myocardial event that can happen immediately after anesthetic induction or during periods of intense sympathetic stimulation such as laryngoscopy, sternotomy, aortic cannulation, or during emergence from anesthesia.